Global Megatrends in Automotive with Focus on Connectivity - Oshchebska, Sofiya; Tyll, Ladislav; Tondlová, Markéta; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
This thesis is dedicated to the analysis of the automotive industry and in particular the innovative topic of car connectivity. The author tries to prove that bringing technology into the car is the logical consequence of globalization and various global megatrends that are influencing the automotive industry. Analysis suggests that by enabling car connectivity and data exchange automotive manufacturers will be able to capture new revenue streams and achieve tremendous levels of car efficiency. Nevertheless this innovation requires automotive OEMs to join forces with other industries such as IT and Telco and work on development of new business models. This work aims at filling the gap in automotive research about car connectivity by defining the size of the business opportunity that it brings, characterizing main connectivity areas and stressing the problems that still need to be resolved. The author provides practical guidance for automakers that plan to set up a connectivity offer, in particular the recommendations on the selection of the right business model, creation of successful value proposition, design of pricing schemes and suggests how to cope with the connectivity challenges.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses